Safety survey by clinical pharmacists on COVID-19 vaccination from a single center in China - Guangfei Wang; Lin Zhu; Yiqing Zhu; Qiaofeng Ye; Xin Yu; Meng Fu; Jinmiao Lu; Xiaoxia Li; Yidie Huang; Junqi Zhang; Jianger Lan; Ziwei Li; et al. (Human Vaccines & Immunotherapeutics, 2021)
This study explored the safety of COVID-19 vaccine (Aikewei) and the role of clinical pharmacists in the implementation of COVID-19 vaccination. A total of 2305 hospital employees in Children’s Hospital of Fudan University in Shanghai, China received the COVID-19 vaccine. The whole process of vaccination was monitored by clinical pharmacists, and the occurrence, types, severity of adverse reactions were recorded in detail. Through the investigation and analysis on the safety of COVID-19 vaccination of the 2305 people, the important role and value of clinical pharmacists in the vaccination process was elaborated. Common adverse reactions included local pain, dizziness and fatigue, with the incidence rates of 2.09%, 0.67% and 0.49%, respectively. Others such as headache, nausea, skin itching, cough, palpitation, dry mouth, hand anesthesia, local induration, muscle soreness, local rash, and chill had incidence rates of less than 0.30%. Three cases of serious adverse events that occurred in this vaccination returned to normal after treatment, with no subsequent discomfort. Clinical pharmacists played an important role in the safety monitoring of COVID-19 vaccination. The safety of the inactivated COVID-19 vaccine is good. Most of the common adverse reactions were mild and tolerable, with generally low incidence. The work of clinical pharmacists is important and can be expanded in the future to ensure the safety of vaccination and to provide better health care service.